2019
DOI: 10.1039/c8dt04935a
|View full text |Cite
|
Sign up to set email alerts
|

Control over coordination self-assembly of flexible, multidentate ligands by stepwise metal coordination of isopyrazole subunits

Abstract: Structural convergence of the self-assembly of flexible oligoisopyrazoles was controlled by stepwise palladium coordination and discrete complexes with structural diversity were selectively generated in a predictable fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The metal coordination behavior of isopyrazole subunits in oligoimine chains also dramatically changed upon oxidation of the ethylene bridge. In a previous study, we have reported that structures of metal complexes with tetraimine ligand 7 varied depending on the metal ions and stoichiometry owing to their structurally flexible nature. , When isopyrazole dimer 7 was complexed with Cd­(NO 3 ) 2 ·4H 2 O in acetonitrile, colorless crystals formulated as [Cd­( 7 ) 2 (OH 2 ) 2 (NO 3 ) 2 ·(CH 3 CN)] n ( 13 ), were obtained in 44% yield (Scheme a). The two-dimensional coordination network structure of complex 13 was determined by single-crystal X-ray analysis .…”
Section: Resultsmentioning
confidence: 99%
“…The metal coordination behavior of isopyrazole subunits in oligoimine chains also dramatically changed upon oxidation of the ethylene bridge. In a previous study, we have reported that structures of metal complexes with tetraimine ligand 7 varied depending on the metal ions and stoichiometry owing to their structurally flexible nature. , When isopyrazole dimer 7 was complexed with Cd­(NO 3 ) 2 ·4H 2 O in acetonitrile, colorless crystals formulated as [Cd­( 7 ) 2 (OH 2 ) 2 (NO 3 ) 2 ·(CH 3 CN)] n ( 13 ), were obtained in 44% yield (Scheme a). The two-dimensional coordination network structure of complex 13 was determined by single-crystal X-ray analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Coordination driven self assembly of these compounds was investigated in depth using tetraimine 15 and Pd 2 ion in solution. 15 When compound 15 was mixed with Pd(CH 3 CN) 4 (BF 4 ) 2 in a molar ratio of 2:1 in acetonitrile d 3 at 60 , discrete complex 18 was formed quantitatively (Scheme 4). The 1 H NMR spectrum exhibited a down eld shifted peak for the ethylene As complex 19 still had uncoordinated imine groups, a further excess amount of palladium ion was added to a solution of 19.…”
Section: Coordination Assemblies Of Polyimine Chainsmentioning
confidence: 99%
“…For example, complexation of 1 with zinc(II) or cadmium(II) ions gave two‐dimensional grid‐like coordination networks where only terminal iminic nitrogen atoms of ligand 1 were utilized as metal binding sites . Ligand 1 changed its coordination number from two to four in discrete palladium(II) complexes . Such unique structural features of 1 prompted us to further explore its coordination behavior with other transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…[1,3] Ligand 1 changed its coordination number from two to four in discrete palladium(II) complexes. [4] Such unique structural features of 1 prompted us to further explore its coordination behavior with other transition metals.…”
Section: Introductionmentioning
confidence: 99%